2019
DOI: 10.1111/jpi.12586
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic inhibition of the tumor suppressor ARHI by light at night‐induced circadian melatonin disruption mediates STAT3‐driven paclitaxel resistance in breast cancer

Abstract: Disruption of circadian time structure and suppression of circadian nocturnal melatonin (MLT) production by exposure to dim light at night (dLAN), as occurs with night shift work and/or disturbed sleep-wake cycles, is associated with a significantly increased risk of breast cancer and resistance to tamoxifen and doxorubicin. Melatonin inhibition of human breast cancer chemoresistance involves mechanisms including suppression of tumor metabolism and inhibition of kinases and transcription factors which are ofte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 68 publications
1
41
0
1
Order By: Relevance
“…Meanwhile, Kim et al have discovered that Oct-4 confers radiation resistance via STAT3 and NF-Bmediated IL-24 production in breast cancer cells [70]. In addition, paclitaxel is widely used as a clinical drug of breast cancer treatment, and phosphorylated STAT3 could mediate Survivin to promote paclitaxel resistance [71].…”
Section: The Role Of Stat3 In Breast Cancer Chemoresistancementioning
confidence: 99%
“…Meanwhile, Kim et al have discovered that Oct-4 confers radiation resistance via STAT3 and NF-Bmediated IL-24 production in breast cancer cells [70]. In addition, paclitaxel is widely used as a clinical drug of breast cancer treatment, and phosphorylated STAT3 could mediate Survivin to promote paclitaxel resistance [71].…”
Section: The Role Of Stat3 In Breast Cancer Chemoresistancementioning
confidence: 99%
“…In the current study, we aimed to understand the mechanisms responsible for paclitaxel resistance involving JAK/STAT3 signaling. Previous studies have reported that STAT3 activation occurs through the IL6 cytokine family 44 . Hartman and colleagues described that IL6 family members IL6 and IL8 are critical for resistance to paclitaxel, due to their stimulation of multiple pathways, including the JAK/STAT3 pathway 45 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently reported that melatonin inhibition of human breast cancer chemoresistance is associated with mechanisms including metabolism switching, and inhibition of specific kinases and transcription factors is often activated in these drug-resistant tumors. 68 These effects seem to be mediated by its MT1 receptor and induction of ARHI protein expression. MT1 activation has also been significantly associated with a good prognosis (higher in luminal A vs. luminal B) and worse prognosis in triple-negative tumors.…”
Section: Of 19mentioning
confidence: 99%